Aesthetic aspects of the teacher's professiogram primary classes. - Sobirjanovna, Dustova Dildora; Fayzullaevich, Abdullaev Sayfulla (The journal of contemporary issues in business and government, 2021)
Following article deals with some aspects of the formation of the esthetic culture of students in the process of teaching the Russian language. It analyzes the features of the upbringing of the esthetic culture of future teachers of primary education.